Islamisasi dan Kristianisasi di Kalangan Orang Asli Temuan, Broga - Sahad, Mohd Nizam; Sa’ari, Che Zarrina (Afkar: Jurnal Akidah dan Pemikiran Islam, 2005)
This article focuses on the process of islamization and christianization among the Temuan Aborigines of Broga. The Temuan Aborigines in Broga had been chosen as the subject of this article since there is a competition between the Islamic da’i and Christian missionary to convert them to either Islam or Christianity. This article also attempts to know the reasons of acceptance and reluctance to embrace these religions among the aborigines.